-2x-6x=-11+3x

Simple and best practice solution for -2x-6x=-11+3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2x-6x=-11+3x equation:


Simplifying
-2x + -6x = -11 + 3x

Combine like terms: -2x + -6x = -8x
-8x = -11 + 3x

Solving
-8x = -11 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-8x + -3x = -11 + 3x + -3x

Combine like terms: -8x + -3x = -11x
-11x = -11 + 3x + -3x

Combine like terms: 3x + -3x = 0
-11x = -11 + 0
-11x = -11

Divide each side by '-11'.
x = 1

Simplifying
x = 1

See similar equations:

| 140-43x-x^2=0 | | -9(v+2)+4v+5=6v+11 | | 2(x+6)=11(x+1/8) | | -2=-2(x-2)+3 | | 2(3.5p+3.5)=7(p+1) | | 3x-22=-8 | | 7x-21/2 | | 2(3.5p+.5)=7(p+1) | | X=9(1/3) | | 40x^2-76+28=0 | | 5x-15/7 | | 6.1t-2.1(t+2)=3(t+1.5) | | 0.7(5x+6)=1.3-(x-3) | | 2x^5/3=-64 | | 5x-15/7/7x-21/2 | | 8a-11a-22=-8 | | 2+3n=1n+12 | | y=(.125-27) | | 2-3(b+4)=8 | | 14x+9=84 | | 8y+8=20 | | 1.75/4.2/3= | | 3m+12=-m-(m+13) | | M-18/2=4 | | m-41= | | 8.75/2/5= | | .5(y+8)=4(y-6) | | (2x+50)+(x+10)=180 | | 2(d+4)=8 | | -2x+2=3(4+x) | | 4(3n-1)=2n+2(5n-2) | | 8x-10=2x+4 |

Equations solver categories